1966
DOI: 10.1152/ajplegacy.1966.210.1.31
|View full text |Cite
|
Sign up to set email alerts
|

Choline-deficiency fatty liver: relation of plasma phospholipids to liver triglycerides

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
45
1

Year Published

1978
1978
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(47 citation statements)
references
References 0 publications
1
45
1
Order By: Relevance
“…Very early studies since the 1930s have shown that high-fat diet-induced hepatic steatosis in both healthy and diabetic animals could be prevented by ingestion of betaine or choline [22,23]. In the rat [24], hamster [25], dog [19] and monkey [26], choline deficiency results in liver dysfunction owing to accumulation of TG [27][28][29][30] and DAGs [31] within the hepatocyte. In rats, fatty liver begins within hours to days after initiation of a choline-deficient diet [32].…”
Section: Animal Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Very early studies since the 1930s have shown that high-fat diet-induced hepatic steatosis in both healthy and diabetic animals could be prevented by ingestion of betaine or choline [22,23]. In the rat [24], hamster [25], dog [19] and monkey [26], choline deficiency results in liver dysfunction owing to accumulation of TG [27][28][29][30] and DAGs [31] within the hepatocyte. In rats, fatty liver begins within hours to days after initiation of a choline-deficient diet [32].…”
Section: Animal Studiesmentioning
confidence: 99%
“…Also, fatty liver induced by a high fat diet in rats could be reversed by daily administration of choline for only 12 days [33]. This may be explained by the impaired release of hepatic TGs in choline-deficiency fatty liver [27]. As previously mentioned, the active synthesis of PC derived from choline is essential for the hepatic synthesis and secretion of VLDL [30].…”
Section: Animal Studiesmentioning
confidence: 99%
“…We also showed that EDI3 regulates cellular migration via the PKCa signaling pathway. Choline metabolism has been intensively discussed in relation to several diseases, including neurological disorders, 3 liver disease, 4,5 and tumor progression. [6][7][8][9][10] With respect to the latter, recent studies have suggested that elevated choline metabolism, including increased phosphocholine (PC) levels, is associated with worse prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…Many patients with steatohepatitis develop some degree of fibrosis within the first years of follow-up (1)(2)(3). The pathogenesis of non-alcoholic fatty liver disease remains unclear.…”
Section: Introductionmentioning
confidence: 99%